On pragmatic demonstratives: The case of pragmatic discourse anaphora in Czech - Šimík, Radek (Proceedings of Sinn und Bedeutung, 2019)
This paper offers a novel syntactico-semantic treatment of canonical and pragmatic demonstratives (the latter type being exemplified by so called affective demonstratives) and within that frame provides an analysis of pragmatic anaphora in Czech. Pragmatic anaphora is understood as an anaphoric relation between the denotation of a demonstrative description and a previous utterance about that denotation. The theoretical proposal is that the syntactic and semantic structure of demonstratives consists of two parts: the D head, interpreted as the iota type shifter (i.e., as a Fregean definite article), and the Dem head, which conveys that the denotation of its nominal complement is related to some entity in extra-linguistic reality or discourse. Due to nanosyntactic principles (superset and elsewhere), demonstratives can either spell out the whole Dem+D structure (canonical demonstratives) or Dem alone (pragmatic demonstratives).